Strengthening Occupational Safety: Evaluation of the OWAS Method in Administrative and Support Workers at the Paredes Ophthalmology Clinic, San Juan de Pasto. (Cuidado y Ocupación Humana, 2024)
Biomechanical risk assessment is a key tool to improve the safety and health of workers. This study focuses on the application of the OWAS (Ovako Working Posture Analyzing System) method to identify and mitigate postural risks in administrative and care workers at the Paredes Ophthalmology Clinic, San Juan de Pasto headquarters; as such, this process was developed in three phases: (1) evaluation of work postures and their classification according to the level of risk, (2) implementation of interventions such as active microbreaks, ergonomics training, and restructuring of workstations, and (3) analysis of the results and measurement of the impact of the interventions, where the findings show that 81% of workers maintain an adequate back posture, although 2% require immediate corrective interventions, and the implemented activities proved to be effective in reducing fatigue, improving posture, and decreasing the risks of musculoskeletal injuries
Keywords: Biomechanical risks; OWAS method; ergonomics; active micro-breaks; occupational safety; care workers